Lyrics and Songs to Improve English Oral Production in 6th and 7th Graders (2017)
ABSTRACT: This action research report is the result of a process in sixth and seventh grade in a public school which has as a main objective to engage students in the English class through the use song lyrics and thereby Improve English Oral Production. The material was designed according to the necessities and interest of students. This report also supports the importance of including students in the development of the classes and materials in order to motivate them. Key words: oral production, song lyrics, motivation.